Cardiovascular health status in Chinese adults in urban areas: Analysis of the Chinese Health Examination Database 2010 - Wu, H.; Sun, Zhonghua; Cao, D.; Wu, L.; Zeng, Q. (Elsevier, 2013)
Background: The American Heart Association (AHA) recently developed definitions of cardiovascular health for adults and children based on 7 cardiovascular disease risk factors or health behaviors. We applied this new construct to examine the cardiovascular health status in adult Chinese urban residents. Methods: Data of 1,012,418 subjects aged 20–65 years (55% were men; mean age, 42.4 years) who received health examination at 58 health examination centers across China was analyzed. The AHA ideal health behaviors index and ideal health factor index were evaluated among the subjects. Results: Only 0.6% of male and 2.6% of female subjects met all 7 health components, and only 39.1% of the subjects met 5 or more components of ideal cardiovascular health. The prevalence of “ideal”, “intermediate” and “poor” cardiovascular health was 1.5%, 33.9% and 64.6%, respectively. Conclusion: About two-thirds of the adult Chinese urban population has “poor” cardiovascular health. Comprehensive individual and population-based interventions must be developed to improve cardiovascular health status in China.